The role and impact of the IL-6 mediated JAK2-STAT1/3 signaling pathway in the pathogenesis of gout - Zhang, Zeng; Wang, Peng; Lei, Tianyi; Guo, Jianwei; Jiang, Yi; Li, Yanhui; Zheng, Jianxiong; Wang, Shunbing; Xu, Haimuzi; Jian, Guilin; Zhang, Quanbo; Qing, Yufeng (Frontiers in Pharmacology, 2025)
BackgroundInterleukin-6 (IL-6) is a pleiotropic cytokine, with specific effects depending on the immune microenvironment. Extensive research has confirmed the pathological roles of the IL-6/JAK2/STAT1/3 signaling pathway in inflammation, autoimmunity, and cancer, as well as its involvement in the pathogenesis of various rheumatic diseases. However, the role and impact of IL-6 as an upstream regulator of the JAK2-STAT1/3 pathway in gout have seldom been reported. This study explores the influence and role of upstream IL-6 in regulating the JAK2-STAT1/3 signaling pathway on gout inflammation, offering new insights for targeted therapeutic interventions and drug development in gout management.Methods and ResultsClinical data and peripheral blood specimens were collected from gout patients and healthy individuals. In vitro and in vivo models of acute gout inflammation were established by stimulating PBMCs, THP-1 cells, and mice with MSU crystals. IL-6 expression was manipulated using IL-6 agonists and IL-6 knockout (KO) mouse technology to investigate the role and impact of the IL-6-mediated JAK2-STAT1/3 signaling pathway in gout models. RT-qPCR, WB, and ELISA were utilized to assess gene and protein expression levels. Paw swelling in mice was measured using a caliper gauge, while HE and IHC staining were conducted to evaluate the inflammatory status of mouse paw pad synovial tissues and detect the positive expression of relevant proteins. Serum IL-6 protein expression levels were significantly elevated in patients with gouty arthritis (GA) compared to healthy individuals, with multifactor logistic regression revealing an odds ratio (OR) of 2.175 for IL-6. In GA patients, mRNA expression of IL-6, JAK2, STAT1/3, and IL-1β was notably lower in the gout group compared to the healthy control (HC) group. Moreover, IL-6, JAK2, STAT1/3, p-JAK2, p-STAT1/3, and IL-1β proteins were markedly higher in the acute gout (AG) group compared to the intercritical gout (IG) and HC groups. Within the IG group, IL-6, JAK2, STAT3, and IL-1β proteins were significantly elevated compared to the HC group, whereas STAT1, p-JAK2, and p-STAT1/3 proteins were significantly lower. The expression of IL-6 protein and JAK2 mRNA showed positive correlations with certain inflammatory markers. In the 2h human blood in vitro gout inflammation model, expressions of IL-1β, IL-6, JAK2 mRNA, and IL-1β, IL-6, JAK2, STAT1/3, p-JAK2, p-STAT1/3 proteins were significantly higher compared to both the blank control and PBS-negative control groups. In the acute gout THP-1 cell model, The 6-hour model group showed significantly higher levels of IL-1β, IL-6, JAK2, STAT1/3 mRNA, and corresponding proteins, including their phosphorylated forms, compared to the blank control group. Additionally, treatment with an IL-6 agonist further increased these expression levels compared to the untreated model group. In the acute gout mouse model, IL-6 KO mice exhibited significantly reduced footpad swelling and swelling index compared to wild-type (WT) mice. HE staining revealed decreased inflammatory cell infiltration in IL-6 KO mice. Furthermore, Compared to 12-hour gout model WT mice, IL-1β, IL-6, JAK2, STAT1/3 mRNA, protein expression, and phosphorylated protein levels were notably decreased in IL-6 KO mice. IHC staining showed reduced positive expression of p-JAK2 and p-STAT1/3 in IL-6 KO mice. At the 24-hour mark, IL-6 mRNA and protein expression levels did not differ significantly between IL-6 KO and WT mice; however, IL-1β mRNA and protein expression, as well as JAK2 and STAT3 mRNA expression, were reduced in IL-6 KO mice, while STAT1 mRNA expression remained similar.ConclusionIL-6 emerges as a potential risk factor for acute gout attacks, with its involvement in the JAK2-STAT1/3 signaling pathway contributing to the inflammation and pathogenesis process of acute gout through positive feedback mechanisms.